Development of an empowerment model for burnout syndrome and quality of nursing work life in Indonesia - Nursalam Nursalam; Rizeki Dwi Fibriansari; Slamet Riyadi Yuwono; Muhammad Hadi; Ferry Efendi; Angeline Bushy (Elsevier, 2018)
Objectives: This study aimed to develop an empowerment model for burnout syndrome and quality of nursing work life (QNWL). Methods: This study adopted a mixed-method cross-sectional approach. The variables included structural empowerment, psychological empowerment, burnout syndrome and QNWL. The population consisted of nurses who have civil servant status in one of the regional hospitals in Indonesia. The participants were recruited using multi-stage sampling measures with 134 respondents. Data were collected using questionnaires, which were then analysed using partial least squares. A focus group discussion was conducted with nurses, chief nurses and the hospital management to identify strategic issues and compile recommendations. Results: Structural empowerment influenced psychological empowerment (path coefficient = 0.440; t = 6.222) and QNWL (path coefficient = 0.345; t = 4.789). Psychological empowerment influenced burnout syndrome (path coefficient = −0.371; t = 4.303), and burnout syndrome influenced QNWL (path coefficient = −0.320; t = 5.102). Structural empowerment increased QNWL by 39.7%. Conclusion: The development of a structural empowerment model by using the indicators of resources, support and information directly influenced the psychological empowerment of the sample of nurses. As an indicator of meaning, psychological empowerment decreased burnout syndrome. In turn, burnout syndrome, as the indicator of personal achievement, could affect the QNWL. Structural empowerment directly influenced the QNWL, particularly within the workplace context. Further studies must be conducted to analyse the effects of empowerment, leadership styles and customer satisfaction. Keywords: Burnout, Empowerment, Nurses, Quality of working life